Integrated system for the monitoring and forecasting of drought events and desertification phenomena, providing appropriate measures for impacts mitigation and water resources usage planning - Monacelli G. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
APAT participates in the Community Initiative Programme INTERREG III B MEDOCC with the project SEDEMED 'Sécheresse et désertification in the Mediterranean Region 'whose aims are the definition of proper studies and mitigation strategies and the organization of an integrated information system supporting water resources planning in order to combat drought and desertification in the frame of an international collaboration. APAT has been involved in activities such as the implementation of a hydro-meteorological database, the extension of the water cycle analysis to the whole Western Mediterranean area, and the identification and application of new drought and desertification indices. It has also improved the existing observation networks and their better organization in pilot projects, and defined appropriate interventions against drought and desertification.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)